A LIGHTWEIGHT INTER-ZONAL AUTHENTICATION PROTOCOL FOR MOVING OBJECTS IN LOW POWERED RF SYSTEMS - Shyamala, C. K.; Rajagopalan, Anand K. (APTIKOM Journal on Computer Science and Information Technologies, 2017)
Automatic identification systems represent a wide classification of devices used primarily in commercialsettings for inventory/logistics control. Familiar examples of such devices are bar codes, magnetic strips, smartcards, RFID (Radio frequency identification) and biometric and voice recognition. Security is especially lax in lowpowered RF (radio frequency) systems communicating through an unsecured radio wave channel. Security representsa critical component for enabling the large scale adoption of automatic identification systems. Providing an effectivesecurity solution for low powered systems is a major area of concern; it directs research towards ?powerconsumption aware? computations in security solutions. This paper proposes a Lightweight Inter-ZonalAuthentication Protocol for moving objects in low powered RF systems. Formal validation and a thorough analysisof the protocol in SPAN security tool reveals its effectiveness and resiliency to attacks?eaves dropping, reader andtag impersonation, replay and desynchronization.